Probiotics, Prebiotics, Synbiotics, and Paraprobiotics as a Therapeutic Alternative for Intestinal Mucositis - Batista, Viviane Lima; da Silva, Tales Fernando; de Jesus, Luís Cláudio Lima; Coelho-Rocha, Nina Dias; Barroso, Fernanda Alvarenga Lima; Tavares, Laisa Macedo; Azevedo, Vasco; Mancha-Agresti, Pamela; Drumond, Mariana Martins (Frontiers in Microbiology, 2020)
Intestinal mucositis, a cytotoxic side effect of the antineoplastic drug 5-fluorouracil (5-FU), is characterized by ulceration, inflammation, diarrhea, and intense abdominal pain, making it an important issue for clinical medicine. Given the seriousness of the problem, therapeutic alternatives have been sought as a means to ameliorate, prevent, and treat this condition. Among the alternatives available to address this side effect of treatment with 5-FU, the most promising has been the use of probiotics, prebiotics, synbiotics, and paraprobiotics. This review addresses the administration of these “biotics” as a therapeutic alternative for intestinal mucositis caused by 5-FU. It describes the effects and benefits related to their use as well as their potential for patient care.